Family supportive supervisor behaviours and turnover intentions: testing a multiple mediation model in the New Zealand hospitality industry. (2nd April 2020) - Nguyen, Le Vinh; Haar, Jarrod; Smollan, Roy
ABSTRACT: Within New Zealand, the turnover rate within the hospitality sector is high, which can be expensive in terms of performance, recruitment and training costs. However, while research asserts an employee's immediate managers can have a strong influence on retention, less is known within the hospitality sector of New Zealand. The present study investigates how family supportive supervision behaviours (FSSB) influence employees' turnover intentions and includes organisational trust and job satisfaction as potential mediators. Using a sample of 149 hospitality workers and the PROCESS macro, our analysis shows that FSSB is negatively related to turnover intentions and positively related to organisational trust and job satisfaction. However, both these job attitudes fully mediate the influence of FSSB and indicate that good leadership builds positive work attitudes and it is these that ultimately shape turnover intentions. Consequently, FSSB should be encouraged so leaders through positively supporting workers work and family commitments can enhance employee attitudes and in turn help retain their hospitality workforce.